Effect of Pullulan Derived from Micrococcus luteus on Preserving Selected Properties of Sunflower Oil - Chalop, Karam Kh; Mousa , Ebtisam F. (Journal of Tropical Crop Science, 2025)
This study evaluates the efficacy of pullulan, a bacterial polysaccharide extracted from a local Micrococcus luteus isolate, in preserving the oxidative stability of unrefined sunflower oil. Using peroxide value (PV) and thiobarbituric acid value (TBA) as metrics. Five treatments were compared against a traditional antioxidant, butylated hydroxytoluene (BHT), and a control. Results demonstrated that the use of 800 ppm pullulan significantly inhibited oxidative degradation of the unrefined sunflower oil, particularly at 20°C storage. Peroxide values for 800 ppm pullulan (1.91 mEq.kg-1 at 20°C; 2.88 mEq.kg-1 at 50°C) were slightly higher than BHT (1.82 and 1.99 mEq.kg-1) but markedly lower than the control (4.49 and 3.59 mEq.kg-1). Thiobarbituric acid values for 800 ppm pullulan (0.38 mg MDA.kg-1 (malondialdehyde) at 2°C at day 40, and at 50°C at day 30, were marginally lower than BHT (0.43 and 0.47 mg MDA.kg-1) and significantly reduced versus the control (0.51 and 1.42 mg MDA.kg-1), respectively.